Mechanical behaviour of a polyvinyl alcohol fibre reinforced engineered cementitious composite (PVA-ECC) using local ingredients. (15th June 2017) - Meng, Dan; Huang, Ting; Zhang, Y.X.; Lee, C.K.
Highlights: A new PVA-ECC with reduced cost and strain capability matching that of steel rebar. Extensive tests on the mechanical behaviour including large number of tensile test. A statistical analysis for the study of the probability distribution. A new finite element model for modelling of flexural behaviour of PVA-ECC beams. Development of a relationship on tensile strength between 2D and 3D specimen. Abstract: A polyvinyl alcohol fibre reinforced engineered cementitious composite (PVA-ECC) using local ingredients is developed, aiming for a reduced cost and a tensile strain capacity matching that of steel reinforcement for commonly used reinforced concrete structures. Experiments are conducted to determine mechanical behaviour of the composite. In addition, a finite element model is developed to simulate the flexural behaviour of PVA-ECC beams, and experimental results are used to calibrate the model. The material models of the PVA-ECC under compression and tension are calibrated using experimental results of uniaxial compression and tension tests. Furthermore, a theoretical relationship on the tensile strength between specimens with two-dimensional and three-dimensional fibre distribution is derived, and accuracy of the simulation is improved by using the theoretical ratio. Agreement between the computed results and the experimental data demonstrates the effectiveness of the finite element model.